2005
DOI: 10.1073/pnas.0408531102
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral corticotropin-releasing factor and urocortin II in intestinal inflammation and motility in terminal ileum

Abstract: Corticotropin-releasing factor (CRF) and the closely related family of neuropeptides urocortins (Ucns) are ancient paracrine-signaling peptides secreted in both the central and peripheral neural circuits. CRF and Ucns released from the CNS (central) regulate a plethora of physiological processes that include food intake, inflammation, and bowel motility and permeability. In the gastrointestinal tract, CRF actions are largely proinflammatory, whereas the effects of the Ucn subtypes can be either pro-or antiinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 47 publications
7
97
2
5
Order By: Relevance
“…When injected centrally or systemically, agonists or antagonists could affect many cell types expressing CRF-Rs, and the generation of mice that lack CRF, Ucns, or their receptors in particular populations of intestinal cells is a daunting task. To circumvent these difficulties, la Fleur et al (5) used RNA interference (RNAi) to silence the expression of CRF and UcnII. RNAi depends on the cellular uptake and processing of double-stranded RNA (dsRNA) into small interfering RNAs (siRNAs) of 21-23 nt by the RNase III enzyme Dicer.…”
mentioning
confidence: 99%
“…When injected centrally or systemically, agonists or antagonists could affect many cell types expressing CRF-Rs, and the generation of mice that lack CRF, Ucns, or their receptors in particular populations of intestinal cells is a daunting task. To circumvent these difficulties, la Fleur et al (5) used RNA interference (RNAi) to silence the expression of CRF and UcnII. RNAi depends on the cellular uptake and processing of double-stranded RNA (dsRNA) into small interfering RNAs (siRNAs) of 21-23 nt by the RNase III enzyme Dicer.…”
mentioning
confidence: 99%
“…In general, the distribution pattern of CRF-positive nerve fi bres of the ovine jejunum resembles those observed in the small intestine of other mammals. Similarly to sheep, in the rodent small intestine a rich network of CRF-expressing nerve fi bres was detected in both the myenteric and submucous plexuses (Wolter, 1984;la Fleur et al, 2005;Liu et al, 2006;Sand et al, 2011). Sand et al (2011) also reported that the circular smooth muscle layer and mucous layer of the rat and guinea-pig small intestine contain moderate numbers of CRF-expressing nerve fi bres.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammalian small intestine VIP-IR/galanin-IR submucous neurons are considered as non-cholinergic secretomotor/vasodilator neurons which innervate mucosal glands and myenteric ganglia (Furness, 2000). Galanin is a strong constrictor of intestinal smooth muscles (Ekblad et al, 1985) and the lack of co-incidence between CRF and galanin in the circular smooth muscle layer may suggest that in the sheep jejunum galanin is not involved in the observed CRF-mediated alterations of small intestine contractility (la Fleur et al, 2005). However, since numerous CRF-IR/galanin-IR nerve fibres were noted in the lamina muscularis mucosae of the ovine jejunum it is possible that both neuropeptides functionally co-operate in the generation of the local movement of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Inhibition of gastric emptying, gastric secretion, gastric contraction and stimulation of colonic motility and defecation have now been well established in adult rats as the hallmarks of neurovisceral motor responses to stressors of psychological, physical, chemical and immunological origin. [10][11][12][13] Members of stress hormone family, more specifically corticotrophin-releasing factor (CRF) and urocortin, have been shown to mimic multifaceted acute responses to stress. 8 Both hormones mediate their actions through CRF-receptor subtype 1 (CRF-R1) and CRF-receptor subtype 2 (CRF-R2).…”
Section: Introductionmentioning
confidence: 99%